Transformasi Peran Serikat Pekerja Bidang Sosial Dalam Mewujudkan Hubungan Industrial Yang Harmonis Dan Sejahtera di PT. Steel Center Indonesia - Taufik Hidayat; Arista Candra Irawati (Jurnal JURISTIC, 2026)
unions in creating harmonious and prosperous industrial relations at PT. Steel Center Indonesia. The main focus is on how social interactions, formal and informal communication mechanisms, and the development of trust between employees and management influence the effectiveness of Collective Labor Agreements (PKB) and the resolution of industrial disputes. The research employs a qualitative descriptive approach, including field studies, observations, and interviews with employees and management. The findings indicate that the strategic role of the union's Social Division through social activities, communication forums, and training enhances relational coordination, strengthens trust, and facilitates the effective implementation of PKB. Trust is identified as a key variable in reducing conflicts, increasing compliance with PKB, and creating a harmonious and productive work environment. The study concludes that the success of industrial relations depends not only on formal regulations but also on the quality of social interactions and employee participation. Recommendations are provided for academics, legal practitioners, company stakeholders, and society to support fair and sustainable industrial relations practices.